Producing Digital Natives with Morals: A Bridge Between Parental Perceptions and Student Needs - Nurdalia, Nurdalia (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Digital natives, who have unrestricted access to information, suffer moral and ethical issues like cyberbullying, disinformation (hoaxes), and identity crises. This has created a gap between parents' idealized view of Islamic education as a moral bulwark and students' needs for a more adaptable and digitally relevant curriculum. Islamic education may be less effective at shaping noble digital character due to this divide. This study aims to identify and analyze in depth (1) how parental perceptions influence the emphasis of Islamic Education materials and methods, and (2) how the relevance of these materials meets students' spiritual and digital literacy needs. This study used a qualitative-descriptive approach with a case study method in an Islamic high school. Data was collected through in-depth interviews (with 15 parents and 10 students), classroom observations, and analysis of curriculum documents at As'adiyah Madrasah No. 21 Kampiri. It was found that most parents have a strong perception that Islamic education should focus on strengthening traditional faith and worship. However, this perception has not yet fully encouraged the integration of Islamic-perspective digital literacy materials (such as social media jurisprudence or online ethics). Thus, pupils believed religious material was insufficient for virtual world problems. This research proposes an Islamic education curriculum model to bridge parents' ideal perceptions and students' current needs, creating morally sound and technologically savvy digital natives.